1986
DOI: 10.1002/bjs.1800731028
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spermatogenesis in testes at risk of torsion

Abstract: The oligospermia observed after unilateral torsion of the spermatic cord could reflect immunological damage to the opposite testis. An alternative explanation, that there may be a pre-existing defect in spermatogenesis, was tested in 20 post-pubertal males with acute torsion. In a prospective study the contralateral testis was biopsied at operation and the histological appearances were related to subsequent testicular function as assessed by seminal analysis 3 months later. Thirteen patients had biopsy evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Such damage is pro portional to torsion time. This hypothesis suggests that early orchiectomy would protect the contralateral testis by preventing or decreasing the release of antibodies by the torsed testis [16], On the other hand, other authors have reported the absence of alterations in the contralateral testis [10,11,13]. We think that this lack of coincidence in these results may be explained by different autoimmune responses to testicular antibody in different strains of rats and guinea pigs.…”
Section: Introductioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Such damage is pro portional to torsion time. This hypothesis suggests that early orchiectomy would protect the contralateral testis by preventing or decreasing the release of antibodies by the torsed testis [16], On the other hand, other authors have reported the absence of alterations in the contralateral testis [10,11,13]. We think that this lack of coincidence in these results may be explained by different autoimmune responses to testicular antibody in different strains of rats and guinea pigs.…”
Section: Introductioncontrasting
confidence: 49%
“…In 1978, Kramp [1] suggested that infertility in pa tients who have undergone testicular torsion may result from an underlying defect in both testicles which have morphological as well as anatomical alterations; this fact also occurs in the normally descended testis of unilateral cryptorchidism [11,19,20], Based on this fact, Horica et al [21] performed bilateral orchiopexy in 7 patients with acute unilateral testicular torsion, and biopsies were made at the same time for both light-microscopic (semi-thin section method) and electron-microscopic examination. Hadziselimovic et al [20] reported that 53% of the patients showed abnormalities which preceded the tor sion, the Sertoli cell syndrome was observed in 7 of the patients, and 4 of them corresponded to the torsed testi cle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different theories have been put forward to explain contralateral testicular damage. The proposed theories include reflex decrease in contralateral testicular blood flow [4, 5, 6, 7, 8, 9], autoimmunity [10, 11], associated congenital anomalies [12, 13]and subclinical torsion attacks of the contralateral testis [14]. Since spermatic cord torsion even in the absence of testis and epididymis is shown to cause contralateral testicular injury and contralateral testicular injury has been demonstrated by DNA flow cytometry within 24 h of ipsilateral testicular torsion [15], autoimmunity, associated congenital anomalies and subclinical torsion attacks of the contralateral testis seem unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…There was minimal anti-sperm and no anti-testis antibody. They concluded that impaired spermatogenesis in acute testicular torsion could be due to an underlying defect [8]. …”
Section: Discussionmentioning
confidence: 99%